2017
DOI: 10.1186/s12964-017-0208-8
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional enzyme ATIC promotes propagation of hepatocellular carcinoma by regulating AMPK-mTOR-S6 K1 signaling

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the cancer types with poor prognosis. To effectively treat HCC, new molecular targets and therapeutic approaches must be identified. 5-aminoimidazole-4-carboxamide ribonucleotide formyltransferase/inosine monophosphate (IMP) cyclohydrolase (ATIC), a bifunctional protein enzyme, catalyzes the last two steps of the de novo purine biosynthetic pathway. Whether ATIC contributes to cancer development remains unclear.MethodsATIC mRNA levels in different types of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 31 publications
6
71
0
Order By: Relevance
“…Indeed, suppression of ATIC expression significantly inhibited the ability of HCC cells to proliferate and migrate through the regulation of the AMPK-mTOR-S6K1 signaling pathway. Therefore, in line with our results, the high expression of ATIC could be positively correlated with adverse prognosis in HCC patients [33].…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, suppression of ATIC expression significantly inhibited the ability of HCC cells to proliferate and migrate through the regulation of the AMPK-mTOR-S6K1 signaling pathway. Therefore, in line with our results, the high expression of ATIC could be positively correlated with adverse prognosis in HCC patients [33].…”
Section: Discussionsupporting
confidence: 88%
“…We also encourage multi-center data to confirm our findings. More laboratory data based on the the mTOR signaling pathway inhibit EIF4E complex and the cap-dependent translation to regulate mRNA translation promote or inhibit the development of tumors as a bifunctional factor/ associate with poor prognosis in breast cancer (Karlsson et al, 2011)/ act as tumor suppressor in SCC (Spilka et al, 2012) TP63 the multiple isoforms of the p63 transcription factor the metabolic pathways, like glucose metabolism, activation of TIGAR and HK II, degradation of PGM, fatty acid oxidation and mitochondrial respiration (Maddocks & Vousden, 2011) activate the autophagy gene network tumorigenesis and tumor suppression/ relate to the oncogenic potential role of SCC/ the genetic variant rs10937405 in TP63 have been found in various ethnic populations like Japanese, Korea, north Indian and British (Wang et al, 2011) population and to be associated with the lung cancer risk BNIP3 a proapoptotic protein belongs to the Bcl-2 family the mitochondrial dysfunction/ the production of ROS/ the repression of mTOR regulate programmed cell death and impart the prodeath activity/ induce autophagy a progression marker in primary human breast cancer/ be linked with poor OS in NSCLC ATIC a cytosolic enzyme in the de novo purine biosynthetic pathway the production of the intermediate FAICAR and IMP (Chan et al, 2015;Greasley et al, 2001) unknown play a significant role in the antitumorigenic effects in the drug of NSCLC/ be related to the poor prognosis of HCC (Jiang et al, 2019;Li et al, 2017) ERO1A a major regulator of PDI PDI dysfunction/ unfolded protein response/ ER stress participate in tumorigenesis a marker of poor prognosis in some tumors, such as glioblastoma, breast cancer and hepatocellular carcinoma/ a poor prognostic factor for OS in NSCLC (Kim et al, 2018) (continued on next page)…”
Section: Discussionmentioning
confidence: 99%
“…We observed that genes involved in cell-cell adhesion (ATIC, RUVBL1, ANXA2, BZW2 and TAGLN2) and cell division (RUVBL1, CCNB1 and DYNLT1) were significantly over-expressed in human HCC and associated with poor patient survival. Both ATIC and BZW2 are considered human oncogenic genes that promote cancer proliferation and migration through mTOR signaling [53,54]. Comparatively, TAGLN2 is known as a tumor suppressor whose protective effects are inhibited when phosphorylated by a cdc2-related serine/threonine protein kinase [55].…”
Section: Plos Onementioning
confidence: 99%